Ceilometer Vaisala CL51 data, Svartberget, Sweden (SE-Svb), 2018-2024 - Larmanou, Eric; Talvinen, Sini (Swedish University of Agricultural Sciences, 2025)
Site description: https://oscar.wmo.int/surface/#/search/station/stationReportDetails/0-20008-0-SVB

Context:
The instrument, a Vaisala ceilometer CL51 measures ceiling or base height of cloud layers. It is installed at the Svartberget ICOS station alongside with other instruments monitoring the atmosphere and the forest ecosystem (Data access: https://data.icos-cp.eu/portal)

Data description:
Raw data converted from DAT (.dat) to NetCDF (.nc) using command line program cl2nc (Kuma, 2024) on python (Kuma et al., 2021), and the converted files are provided. Data covers a time period between 23rd of July 2018 (14:00) and 31st of December 2024 (23:00).
The variables included in the .nc files as well as the description and units can be found in the file Variable_description.tsv (tab separated values). Please see Vaisala CL51 user guide for more information regarding the variables: https://docs.vaisala.com/r/M210801EN-J/en-US (last access: 3rd February 2025) or https://github.com/peterkuma/cl2nc (last access: 3rd February 2025)

The files are hourly files with the following naming AYMMDDHH in which the first two digits (AY) refer to the year i.e. A8 = 2018, A9 = 2019, A0= 2020, A1 = 2021, A2 = 2022, A3 = 2023 and A4 = 2024. The rest six (6) digits refer to month (MM), day (DD) and hour of the day (HH).

Data resolution is approximately 10 seconds (can be set between 6-120 seconds based on the software manual) leading to 600 observations per hour if no data is missing

Some variables (layer, layer_cloud_amount, layer_height, level, sky_detection_status, time, window_contamination) are sometimes missing, mostly in the older files. They are related to the "layer"-variables and are only produced if the ceilometers Sky Condition Algorithm is active, which has not been the case especially in the beginning.

References
Kuma, P.: cl2nc (3.7.1), Zenodo, https://doi.org/10.5281/zenodo.14548122, 2024.
Kuma, P., McDonald, A. J., Morgenstern, O., Querel, R., Silber, I., and Flynn, C. J.: Ground-based lidar processing and simulator framework for comparing models and observations (ALCF 1.0), Geosci. Model Dev., 14, 43–72, https://doi.org/10.5194/gmd-14-43-2021, 2021.

The data files are provided in NetCDF format (https://www.unidata.ucar.edu/software/netcdf/)

Plats beskrivning: https://oscar.wmo.int/surface/#/search/station/stationReportDetails/0-20008-0-SVB

Sammanhang:
Instrumentet, en Vaisala ceilometers CL51 mäter molntoppen eller molnbasen på molnskikten. Den är installerad vid Svartbergets ICOS-station tillsammans med andra instrument som övervakar atmosfären och skogens ekosystem (Dataåtkomst: https://data.icos-cp.eu/portal)

För mer information, se den engelska versionen.
Ceilometer Vaisala CL51 data, Svartberget, Sweden (SE-Svb), 2018-2024
Keywords: CLOUDS; CLOUD CEILING; LIDAR; ceilometers; cloud cover; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap